Substantive Justice in Consumer Protection Law: A Comparative Study of Regulations in Indonesia and Russia - Wibowo, Dwi Edi; Wibowo, Aurea Qonita; Begishev, Ildar (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Consumer protection is a crucial aspect in maintaining the balance between business interests and the rights of consumers. Legal regulations must embody the principles of substantive justice, ensuring not only formal legal procedures but also tangible outcomes that directly benefit society. the application of substantive justice theory within consumer protection regulations in Indonesia and Russia, two countries with distinct legal systems and socio-political contexts.Purposes of the Research: The purpose of this study is to analyze the extent to which consumer protection regulations in Indonesia and Russia have implemented the principles of substantive justice, and to identify points of convergence as well as divergence between the two systems.Methods of the Research: This research employs a normative legal method with a comparative approach. Data are obtained through statutory analysis, examination of relevant provisions, and a review of scholarly literature on substantive justice. The research emphasizes how the respective legal frameworks address consumer rights, business obligations, and dispute resolution mechanisms.Results Main Findings of the Research: The findings reveal that Indonesia, through Law Number 8 of 1999 on Consumer Protection, primarily emphasizes the distribution of rights, obligations, and accessible dispute resolution mechanisms. Meanwhile, Russia, under the Law on Protection of Consumer Rights Number 2300-1 of 1992, places greater weight on comprehensive compensation, including moral damages. The originality of this research lies in its comparative analysis of the application of substantive justice theory between Indonesia and Russia, a juxtaposition rarely explored in consumer law scholarship. The study contributes to the academic discourse by demonstrating that the realization of substantive justice depends not only on statutory provisions but also on the effectiveness of legal enforcement and public legal awareness.